2006
DOI: 10.1038/sj.bjc.6603527
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of postmenopausal hormone use and ovarian cancer risk

Abstract: The relationship between postmenopausal hormone use (PMH) and ovarian cancer risk is unclear, particularly for specific hormone formulations, but recent studies suggest that there is a positive association. We conducted a prospective observational study with 82 905 postmenopausal women, including 389 ovarian cancers, in the Nurses' Health Study from 1976 to 2002. Compared with never users of PMH, both current and past users of X5 years had a significantly elevated risk of ovarian cancer (RR ¼ 1.41, 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 42 publications
10
80
1
3
Order By: Relevance
“…In contrast, several studies published since this metaanalysis have suggested that long-term use of E-alone may increase risk [5,7,15,29,30]. In a cohort study, Lacey et al detected a significantly increased risk of ovarian cancer in women who had used estrogen therapy for 10-19 years (HR=1.8, 95% CI: 1.1-3.0) or more than 20 years (HR=3.2, 95% CI: 1.7-5.7) compared to never users [15].…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…In contrast, several studies published since this metaanalysis have suggested that long-term use of E-alone may increase risk [5,7,15,29,30]. In a cohort study, Lacey et al detected a significantly increased risk of ovarian cancer in women who had used estrogen therapy for 10-19 years (HR=1.8, 95% CI: 1.1-3.0) or more than 20 years (HR=3.2, 95% CI: 1.7-5.7) compared to never users [15].…”
Section: Discussionmentioning
confidence: 60%
“…In a cohort study, Lacey et al detected a significantly increased risk of ovarian cancer in women who had used estrogen therapy for 10-19 years (HR=1.8, 95% CI: 1.1-3.0) or more than 20 years (HR=3.2, 95% CI: 1.7-5.7) compared to never users [15]. Danforth and colleagues detected a two-fold increased risk among users of 5 or more years duration [5], and the recent findings from the Million Women study also suggested an elevated risk with long-duration (≥5 years) of use (relative risk-1.53, 95% CI 1.27-1.84). In the current data, we detected a statistically significant increased risk of ovarian cancer associated with E-alone use, though we could demonstrate no clear dose-response relationship with increasing duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations